2003
DOI: 10.1152/ajprenal.00378.2002
|View full text |Cite
|
Sign up to set email alerts
|

Obstruction-induced changes in urinary bladder smooth muscle contractility: a role for Rho kinase

Abstract: Detrusor smooth muscle (DSM) undergoes hypertrophy after partial bladder outlet obstruction (PBOO) in male rabbits, as it does in men with PBOO induced by benign prostatic hyperplasia. Despite detrusor hypertrophy, some bladders are severely dysfunctional (decompensated). In this study, the rabbit model for PBOO was used to determine the biochemical regulation of the contractile apparatus and force maintenance by the detrusor from decompensated bladders (DB). Bladders from sham-operated rabbits served as a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
122
2
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(128 citation statements)
references
References 30 publications
3
122
2
1
Order By: Relevance
“…This is in agreement with previous work wherein identification of these proteins has also been demonstrated [25,27,30,31,37,45]. In addition, recent reports demonstrate that ROKβ is partly responsible for the high degree of force maintenance in the detrusor smooth muscle in overactive bladders [30][31][32]. Our experiments revealed that both ROKα and ROKβ are expressed at lower levels in the urethra compared to the detrusor and trigone.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in agreement with previous work wherein identification of these proteins has also been demonstrated [25,27,30,31,37,45]. In addition, recent reports demonstrate that ROKβ is partly responsible for the high degree of force maintenance in the detrusor smooth muscle in overactive bladders [30][31][32]. Our experiments revealed that both ROKα and ROKβ are expressed at lower levels in the urethra compared to the detrusor and trigone.…”
Section: Discussionsupporting
confidence: 93%
“…In human, rat, rabbit and guinea pig bladder, the Rho-kinase pathway represents an important regulator of smooth muscle activity and tone [25,[27][28][29][30][31][32]. The prototype Rho-kinase inhibitor Y-27632 has been shown to attenuate contractions of bladder smooth muscle evoked by CCh, through the decrease of Ca 2+ sensitivity of the contractile apparatus [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 There is also a possibility that a multisystem dysfunction of Rho kinase exists and leads to both ED and LUTS. 40 Rho kinase has further been shown to have a role in hypertension and its expression correlates to aging, which provides a partial explanation not only for the relationship between LUTS and ED, but also for the connection of LUTS, ED and hypertension. 41 Pelvic atherosclerosis An additional mechanism is diffuse atherosclerosis of blood vessels supplying prostate, penis and bladder.…”
Section: Luts and Ed: Pathophysiological Correlationsmentioning
confidence: 96%
“…61 Several studies have shown increased Rho-kinase activity in the prostates of hypertensive rats, 62 and the detrusor and corpus cavernosum of rabbits with partial BOO. 63,64 Increased Rho-kinase activity has also been seen in diabetes and vascular smooth muscle in hypertension. 65,66 In addition, Rho-kinase inhibitors have been shown to alleviate ED in rats, with a potentiated effect with concomitant use of PDE5 inhibitors.…”
Section: Ah and The Metabolic Syndromementioning
confidence: 99%